Analysis of Language and Cultural Shifts in The Technological Era in Kelambir V Kebun Village, Hamparan Perak - Yunus, Rusyda Nazhirah; Sisi Rosida (JOLADU: Journal of Language Education, 2023)
This research on language shift in the Kelambir V Village community aims to describe the form of community language use based on the age domain, namely children, adolescents, and adults. The type of research used by researchers is descriptive quantitative. Based on the results of the analysis, it can be concluded that the Deli Malay language in Kelambir V Village can be said to still survive. In language selection, the largest use of Deli Malay language is in the family domain, the second largest user is in the neighborhood domain, the third in the work domain, and the fourth in the religious domain. In the Deli Malay community, the use of Deli Malay is more dominantly used in the family sphere and the realm of neighbors which is type (R), while in the realm of work and the realm of religion which is type (T) is more dominant in using mixed languages (Deli Malay - Indonesian).